Headaches in a Horseback Rider. (20th March 2023) - Hunter, Nicole; Kostowniak, Christian; Hamayel, Abdallah; Bliss, Aaron; Lakin, Hunter; Tan, Josenia; Proia, Laurie
Abstract : An immunocompetent woman presented with headaches. She previouslyworked at a farm in upstate New York. Brain MRI noted pituitary enlargement and neurosurgerypursued trans-sphenoidal pituitary biopsy. Histopathology revealed ill-defined granulomaswith clusters of yeast, consistent with Histoplasma.